Feeding Anglo-Saxon England: a bioarchaeological dataset for the study of early medieval agriculture (Data paper) - McKerracher, M; Hamerow, H; Bogaard, A; Ramsey, CB; Charles, M; Forster, E; Hodgson, J; Holmes, M; Neil, S; Roushannafas, T; Stroud, E; Thomas, R (Council for British Archaeology, 2023)
The FeedSax project combined bioarchaeological data with evidence from settlement archaeology to investigate how, when and why the expansion of arable farming occurred between the 8th-13th centuries in England. It has generated and released a vast, multi-faceted archaeological dataset both to underpin its own published findings and to support further research.